Solar Installations & Their Occupational Risks. (September 2021) - Duroha, Jesse C.; Macht, Gretchen A.
With the solar industry's rapid growth, it is crucial to continuously review and assess the occupational risks associated with photovoltaic (PV) installations. PV installers are exposed to severe occupational risks, including but not limited to electrocution, heat stress, fall accidents, and manual handling risks. However, it is unclear what research is being done to mitigate these risks and where more research is required. Therefore, this paper performs a systematic literature review using the Scopus database to comprehensively review and identify: (1) the current knowledge available regarding the occupational risks associated with PV installations, (2) the health and safety effects these risks have on PV installers, (3) the research being done to mitigate them, and (4) the knowledge gaps for future research. This research can guide areas for future research concerning occupational safety and health in the PV installation sector.